2020
DOI: 10.21203/rs.3.rs-26258/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on orthopedic surgical practice: international study

Abstract: Purpose The purpose of this study was to assess the impact of the COVID-19 pandemic on the clinical practice in orthopedic units.Methods An online survey was sent by e-mail to orthopedic surgeons practicing in different parts of the world.Results This study showed that orthopedic surgery plan management was adapted to respond more effectively to the COVOD-19 pandemic while maintaining the continuity of health care and ensuring protection of medical staff and patients. Among the introduced measures, elective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The Orthopedic surgeons had received relevant training on protective measures, and they were frequently washing hands and wearing masks; however, there was an overall shortage of personal protective equipment. The Orthopedic surgeons had experienced extreme stress, and anxiety while performing their duties during COVID-19 pandemic (Meraghni et al, 2020). Jahanzeb et al (2020) conducted a study on the orthopedic surgeon in Pakistan, and revealed interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“…The Orthopedic surgeons had received relevant training on protective measures, and they were frequently washing hands and wearing masks; however, there was an overall shortage of personal protective equipment. The Orthopedic surgeons had experienced extreme stress, and anxiety while performing their duties during COVID-19 pandemic (Meraghni et al, 2020). Jahanzeb et al (2020) conducted a study on the orthopedic surgeon in Pakistan, and revealed interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The pandemic has had a massive effect on the delivery of orthopaedic and trauma care services across the globe. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Non-urgent, elective surgeries have been deferred, and there has been an increased emphasis on non-operative management of fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 virus has caused an unprecedented, catastrophic pandemic, which has adversely affected healthcare systems globally (1). As a result, the number of surgical procedures in hospitals has decreased substantially, owing in part to the potential risk of viral transmission through aerosols (2,3). Orthopaedic surgical procedures (OSP) are considered as aerosol generating procedures (AGP), chiefly due to the use of high-speed drilling and cutting tools, electrocautery and wound lavage systems (4,5).…”
Section: Introductionmentioning
confidence: 99%